Design, synthesis and characterization of fused bithiazole- and dithiophene-based low bandgap thienylenevinylene copolymers. Issue 41 (30th September 2021) - Patra, Dhananjaya; Comí, Marc; Zhang, Xianhe; Kini, Gururaj P.; Udayakantha, Malsha; Kalin, Alexander J.; Banerjee, Sarbajit; Fang, Lei; Guo, Xugang; Al-Hashimi, Mohammed
Abstract : The electron-deficient thiazole moiety has high planarity and effective π–π stacking, which leads to the reduction in the energy levels, exhibiting promising charge carrier mobilities. Abstract : The structural rigidity of fused units in the polymer backbone, in addition to the resulting stabilizing effect of the quinoidal structure, and tunable electronic properties have played a key role in promoting highly-ordered π-stacking moieties, exhibiting promising charge carrier mobilities. The electron-deficient thiazole moiety shows high planarity and effective π–π stacking, which leads to the reduction in the energy levels of the highest occupied and lowest unoccupied molecular orbitals (HOMO/LUMO), and ideally enhances the electron charge mobility. Four heterocycle-based monomers BTzS, BTzSe, DTS, and DTG based on fused bithiazole and dithiophene units incorporated with sulfur, selenium, silicon, and germanium as the bridging atoms were synthesized and characterized. The monomers were copolymerized with the electron-rich alkylated thienylenevinylene (TV) unit to afford copolymers P1–P4 . The thermal, optical, and electrochemical properties and crystallinity of the copolymers were thoroughly investigated. Extensive OFET device optimization using different solvents and annealing temperatures resulted in the best charge mobility of 0.09 cm 2 V −1 s −1 for the electron-deficient bithiazole BTzS copolymer P1 and 0.36 cm 2 V −1 s −1 for the DTS copolymer P3 .